USING THE GOOGLE CLASSROOM APPLICATION IN CRITICAL READING COURSES, UNIVERSITY OF INDRAPRASTA PGRI JAKARTA - Tita Puspitasari (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The development of technology, information, and communication that is increasingly rapidly in the era of globalization as it is today can no longer avoid the influence on various fields. During the COVID-19 pandemic, which affected the education sector, it changed learning activities from face-to-face to online learning. Lecturers are required to find ways to design learning media as innovations using online media. One of the online learning media that is currently developing and starting to be used is Google Classroom. Google Classroom is a special application that is used for online learning carried out remotely and can be used anywhere. The purpose of this study is to utilize the use of the Google Classroom application in the student learning process in the Critical Reading course for the RH class, Indraprasta University, PGRI Jakarta. The type of research used is literature/library study and observation through interviews with students. The results obtained proved effective on student independence, lecturer creativity and optimal learning outcomes.